Investigation of Poly-Si Gated, Al2O3-Based High-k Dielectrics on 4H-SiC - Ziegler, Johannes; Scholten, Dick; Bartolf, Holger; Voznyi, Andrii; Rabinzohn, Patrick; Schulze, Jörg (Trans Tech Publications Ltd, 2025)
In this paper, we investigate the electrical and structural characteristics of Al2O3-based high-k gate dielectrics, which were integrated into a gate-first, high-temperature manufacturing process having comparable thermal budget as needed in 4H-SiC metal-oxide-semiconductor field-effect transistor (MOSFET) production. MOS capacitors were chosen as test devices to examine the electrical performance in terms of current-voltage (I-V) and capacitance-voltage (C-V) behavior. Remarkably, even after processing temperatures of up to 1,000 °C for ohmic contact formation, the Al2O3 layers revealed highly uniform breakdown characteristics, low C-V hysteresis and a flat-band voltage (VFB) that closely aligns with the theoretical value. Time-dependent dielectric breakdown (TDDB) measurements of the Al2O3 MOS capacitors, however, showed a clear reliability disadvantage concerning the intrinsic dielectric lifetime when comparing with the SiO2 counterpart from commercial SiC production. Finally, to better understand the electrical behavior, transmission electron microscopy (TEM) analysis was conducted, pointing out that high-temperature processing causes the Al2O3 films to transition from an amorphous state to an ordered, polycrystalline structure.
CRIS-Team Scopus Importer:2025-10-16
Keywords: atomic layer deposition; high-k gate dielectrics; MOS capacitor; poly-Si gate electrode; time-dependent dielectric breakdown; transmission electron microscopy